Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Gojek Pada Masa Pandemi Covid-19 di Kota Bandung - Amel Aprillia; Dian Candra Fatihah (STKIP PGRI SITUBONDO, 2021)
Abstract: This study was conducted with the aim of knowing how much influence service quality has on Gojek’s consumer satisfaction during the Covid-19 pandemic in Bandung City. The research method use is a quantitative method with a descriptive and associative approach. In this study, to collect data using questionnaires distributed to Gojek consumers in Bandung, which were processed using SPSS V28.0. The data analysis technique used is normality test, simple linear regression analysis test, and T test. In the result of the pearson product moment correlation coefficient, it was obtained that it was worth 0.724, which means the level of relationship between service quality variable ad customer satisfaction variable can be stated to be positively correlated. And the result of hypothesis testing using the T test with a significant value is t count of 4.844 and t tabel of 2.036 then Ho is rejected and Ha is accepted. The advice that the author gives is that Gojek’s must always prioritize service quality to customer satisfaction so that consumer always give trust and more value to Gojek Drivers. Keywords: Service Quality, Customer Satisfaction